THE EFFECT OF FINANCIAL PERFORMANCE ON FIRM VALUE WITH CORPORATE SOCIAL RESPONSIBILITY AS A MODERATING VARIABLE - Estu Widarwati; Nunik Nurmalasari; Lulu Noviawati (STIESA Press, 2022)
This study aims to determine and analyze the effect of financial performance on firm value with CSR as a moderating variable. Companies need to pay attention to financial performance which is one of the views of investors in assessing the company. With high financial performance and company value, of course, it can attract investors to invest. In addition, CSR in the company is also very important, because it can add to the company's image. This research method uses purposive sampling technique. The number of samples is 16 banking companies listed on the IDX in 2020-2021. The variables used are financial performance as proxied by ROA, firm value as proxied by Tobins'Q and CSR as a proxy by CSDI as moderation. The analytical tool used is eviews. The results show that (1) financial performance has a significant effect on firm value, (2) Corporate Social Responsibility cannot moderate the effect of financial performance on firm value. Companies must pay attention to financial performance (profitability) so that companies can develop and increase company value. Although CSR in this study has no effect, companies must still pay attention to CSR because it can add to the company's image.